PENDIDIKAN KARAKTER KAJIAN KONSEPTUAL DAN KEMUNGKINAN IMPLEMENTASI - I G. A. K. Wardani (LPPM Universitas Terbuka, 2009)
Facing the rapid changing world, concern on the future of the nation is increasing. This is due to the fact that a lot of practices in schools, families, as welf as in society do not conform with the etical conduct, moral, and good manner that are universially accepted by human being. Therefore, all people who concern on the future of the nation, especially educators, should aware of the importance of character education, in order to save the future generation from moral degradation. Related to the problem, this aims at trigerring the awareness of educator to the importance of character education, by discussing the conceptual meanings ( what, why, and how) of character education, then followed by the possibility for implementation, and ended with the implication on education and teacher education.